Pengaruh Hambatan Samping terhadap Kapasitas Dasar Jalan Perkotaan Kota Balikpapan dengan Pendekatan Simulasi Mikroskopik - Hadid, Muhammad; Putri, Arum Prastiyo (Departemen Teknik Infrastruktur Sipil Institut Teknologi Sepuluh Nopember Surabaya, 2021)
The objective of this research is to show the impact of the side friction to ideal capacity on the urban road based on a microscopic simulation approach. Simulation using software PTV VISSIM. the kind of side frictions that use are parking/stop vehicle (PSV), slow vehicle (SMW), and entry/exit vehicle (EEV). Simulation divided into 2 steps are the first is to gain the basic model and the second is to gain the impact of side friction to ideal capacity. The result shows that the side friction that gives the highest impact to ideal capacity is entry/exit vehicle (EEV), especially on an undivided road. The other result shows that the combination of side friction is not give a cumulative impact on decreasing ideal capacity. That indicates that the combination side friction simulation has a proportional impact on the decreasing of ideal capacity. This research can be an alternative method to analyze the urban traffic characteristics in Indonesia.